2020
DOI: 10.3390/molecules25143289
|View full text |Cite
|
Sign up to set email alerts
|

EPA/DHA Concentrate by Urea Complexation Decreases Hyperinsulinemia and Increases Plin5 in the Liver of Mice Fed a High-Fat Diet

Abstract: Dietary intake of eicosapentaenoic/docosahexaenoic acid (EPA/DHA) reduces insulin resistance and hepatic manifestations through the regulation of metabolism in the liver. Obese mice present insulin resistance and lipid accumulation in intracellular lipid droplets (LDs). LD-associated proteins perilipin (Plin) have an essential role in both adipogenesis and lipolysis; Plin5 regulates lipolysis and thus contributes to fat oxidation. The purpose of this study was to compare the effects of deodorized refined salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Table 1 shows the DRCSO characterization by physical and chemical analyses. Values obtained for the free fatty acids (FFA) content, peroxide value (PV), p -anisidine value (AV) and total oxidation (TOTOX) (0.20 ± 0.00 g oleic acid/100 g oil; 0.40 ± 0.00 meq active oxygen/kg oil; 1.13 ± 0.02; and 1.93 ± 0.02, respectively) reveal low lipid oxidation and hydrolytic development, which agrees with previous research on different kinds of fish oils, including salmon oil [ 29 , 30 , 31 ]. Notably, the present DRCSO oxidation values found are under the limits recommended for human consumption (i.e., 15–20 for the AV value) [ 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Table 1 shows the DRCSO characterization by physical and chemical analyses. Values obtained for the free fatty acids (FFA) content, peroxide value (PV), p -anisidine value (AV) and total oxidation (TOTOX) (0.20 ± 0.00 g oleic acid/100 g oil; 0.40 ± 0.00 meq active oxygen/kg oil; 1.13 ± 0.02; and 1.93 ± 0.02, respectively) reveal low lipid oxidation and hydrolytic development, which agrees with previous research on different kinds of fish oils, including salmon oil [ 29 , 30 , 31 ]. Notably, the present DRCSO oxidation values found are under the limits recommended for human consumption (i.e., 15–20 for the AV value) [ 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 90%
“…For the DRCSO, the AV was lower than the 20-unit limit established by Codex and GOED. In the literature, values of 6.84 ± 0.46, 5.14 ± 1.02 and 3.70 ± 0.33 were observed in refined salmon oil [ 29 , 31 , 39 ]. In addition, the DRCSO also complies with the Canadian legislation NHP Fish Oil, PhEur Fish Oil Types I and II, Br Pharm, Fish Oil, Australia Natural Fish Oil Types I and II and USP Fish oil [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the study also found that liver glycogen content significantly increased with increasing dietary lipid levels, which was consistent with the histomorphology reflection of the liver. LD-associated proteins perilipin (plin) are crucial for both adipogenesis and lipolysis [ 31 ]. Perilipin 3 covers nascent neutral lipids and affects the ability of the cell to accumulate TG [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The C. cohnii biomass production step was followed by biomass saponification and lipid fractionation using the urea complexation method, which has been successfully used to concentrate PUFA in diverse lipidic materials, including vegetable and fish microalgal oils [11,16,27,33].…”
Section: Cohnii Faee Fractionationmentioning
confidence: 99%
“…Therefore, the FFA obtained after the saponification step was converted into EE before the addition of urea (Figure 1), since ethanol is less toxic than methanol [49]. Indeed, several authors have enriched PUFA EE, rather than PUFA methyl ester (ME), from lipidic samples [11,50,51]. The main sources of EPA and DHA are currently commercial formulations based on oral ethyl ester [10].…”
Section: Cohnii Faee Fractionationmentioning
confidence: 99%